2019
DOI: 10.33048/semi.2019.16.123
|View full text |Cite
|
Sign up to set email alerts
|

Lattices in generative classes

Abstract: We define and study lattices in generative classes associated with generic structures. It is shown that these lattices can be non-distributive and, moreover, arbitrary enough. Heights and wights of the lattices are described. A model-theoretic criterion for the linear ordering is proved and these linear orders are described. Boolean algebras generated by the considered lattices are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Using these calculi, in Section 5, we introduce the notion of meeting of cardinality contradiction and, for given generative class, characterize the existence of a generic structure. In section 6 [34] we define and study lattices in generative classes associated with generic structures. It is shown that these lattices can be non-distributive and, moreover, sufficiently arbitrary enough.…”
Section: Preliminariesmentioning
confidence: 99%
“…Using these calculi, in Section 5, we introduce the notion of meeting of cardinality contradiction and, for given generative class, characterize the existence of a generic structure. In section 6 [34] we define and study lattices in generative classes associated with generic structures. It is shown that these lattices can be non-distributive and, moreover, sufficiently arbitrary enough.…”
Section: Preliminariesmentioning
confidence: 99%